2012
DOI: 10.1051/0004-6361/201219955
|View full text |Cite
|
Sign up to set email alerts
|

BR1202–0725: an extreme multiple merger atz= 4.7

Abstract: The radio-quiet quasar BR1202-0725 (z = 4.695) is a remarkable source with a bright northwest (NW) companion detected at submillimeter and radio wavelengths but invisible in the optical. In the absence of amplification by gravitational lensing, BR1202−0725 would be the most luminous binary CO and far-infrared (far-IR) source in the Universe. In this paper, we report observations with the IRAM Plateau de Bure interferometer of BR1202-0725 in the redshifted emission of the CO(5-4) and (7-6) lines, the [C I]( 3 P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 55 publications
7
74
0
Order By: Relevance
“…The corrections and uncertainties ensure that a direct estimate of n and G 0 is not meaningful, but we can compare the general location of the HLS0918 components with other observed galaxy populations. The integrated emission from HLS0918 is similar to local ULIRGs and less than 0.5 dex from three well-studied, high-redshift sources: the SMG HFLS3 (z = 6.34; Riechers et al 2013), the quasar host galaxy BRI1335-0417 (z = 4.41; Riechers et al 2008), and BRI1202-0725N, the SMG component of a quasar/SMG merger at z = 4.7, which cannot be deblended from its companion at some wavelengths (Momjian et al 2005;Salomé et al 2012). In contrast, two other well-studied high-z SMGs, SMMJ2135 (z = 2.3; Swinbank et al 2010;Ivison et al 2010b) and LESSJ0332 (z = 4.76;De Breuck et al 2011), are more than half a magnitude larger in L [C ii] /L FIR , which is interpreted as an atomic gas density more than a magnitude lower than that of HLS0918.…”
Section: Physical Properties Of the Pdrmentioning
confidence: 78%
“…The corrections and uncertainties ensure that a direct estimate of n and G 0 is not meaningful, but we can compare the general location of the HLS0918 components with other observed galaxy populations. The integrated emission from HLS0918 is similar to local ULIRGs and less than 0.5 dex from three well-studied, high-redshift sources: the SMG HFLS3 (z = 6.34; Riechers et al 2013), the quasar host galaxy BRI1335-0417 (z = 4.41; Riechers et al 2008), and BRI1202-0725N, the SMG component of a quasar/SMG merger at z = 4.7, which cannot be deblended from its companion at some wavelengths (Momjian et al 2005;Salomé et al 2012). In contrast, two other well-studied high-z SMGs, SMMJ2135 (z = 2.3; Swinbank et al 2010;Ivison et al 2010b) and LESSJ0332 (z = 4.76;De Breuck et al 2011), are more than half a magnitude larger in L [C ii] /L FIR , which is interpreted as an atomic gas density more than a magnitude lower than that of HLS0918.…”
Section: Physical Properties Of the Pdrmentioning
confidence: 78%
“…Xia et al 2012). In addition, one can look at the submm output of dust-obscured QSOs to search for evidence of recent mergers (e.g., Carilli et al 2002;Krips et al 2005;Riechers et al 2008;Salomé et al 2012;Carniani et al 2013), and outflows can be observed in bright CO lines (e.g., Veilleux et al 2013;Sun et al 2014;Feruglio et al 2015;Spilker et al 2018).…”
mentioning
confidence: 99%
“…By including other published SMGs at different redshifts (Magdis et al 2011;Combes et al 2012;Salomé et al 2012;Walter et al 2012;Riechers et al 2013), we have plotted the L CO(1-0) /M dust versus redshift for all of them in the right panel of Fig. 12 similarly to Tan et al (2014).…”
Section: Star Formation and The Molecular Gas Content In High-redshifmentioning
confidence: 99%